Analisis Strategi Pemasaran dan Kelayakan Bisnis Ritel Sepatu: Studi Kasus Toko Sepatu benzboysclub__ - Renaldi Salman Muhar; Hani Humaeriyah (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the feasibility of establishing a retail business plan "Shoe Store [benzboysclub__]" from various business aspects. The main focus of the study includes analysis of consumer behavior, marketing strategies, human resources, and financial projections to determine business sustainability amidst dynamic fashion trends. Data was collected through a perception survey of 30 respondents to measure product quality, price, and purchasing decisions. The results of the analysis indicate that consumers highly prioritize comfort, product durability, and complete size availability as the main advantages of a physical store. From a financial aspect, an initial investment of IDR 70,000,000 is projected to reach Break Even Point (BEP) in approximately 7 months with an estimated monthly net profit of IDR 10,000,000. Overall, based on the analysis of market, operational, legal, and financial aspects, this business plan is declared FEASIBLE to be implemented. To increase market reach, the use of an omnichannel sales system and digital stock management is recommended.